PENGARUH JUMLAH PIPA TERHADAP LAJU PELEPASAN KALOR PADA KOLEKTOR SURYA ABSORBER BATU GRANIT - Wirawan, Made; Mirmanto, Mirmanto; Sutanto, Rudy (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2015)
Fossil energies as un-renewable energies have been getting depletion. Therefore, the use of alternative energy should be raised. One of the alternative energies is solar energy. Solar energy does not pollute the environment and is categorized as a renewable energy which is free and plentiful.   In this research, the solar energy was used to heat water by operating granite absorber solar collectors. The water was flowed naturally from a higher tank and adjusted using a valve fitted at the outlet of the collector.  The volumetric rates of the water were 200, 250 and 300 cc/minutes. Two identical solar collectors with an overall dimension of 0,8 m x 1 m x 0,1 m were placed under the sun and faced to the North with an inclination angle of 15°. One collector contained 5 parallel pipes and the other comprised 7 parallel pipes.  Data obtained in this research are glass cover temperatures, an ambient temperature, absorber temperatures, inlet and outlet water temperatures, and water volumetric rates. The results show that the 7 parallel pipe collector products higher outlet water temperature and energy than the 5 parallel pipe collector. Consequently, in the process of energy removal/discharge, the heat stored in the 7 parallel pipe collector runs out quicker.